2016
DOI: 10.1097/rli.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-Flight Magnetic Resonance Angiography With Sparse Undersampling and Iterative Reconstruction

Abstract: Sparse TOF can achieve better image quality relative to PI TOF at higher acceleration factors. The diagnostic quality of distal branches (A2/3, M4, P4) was maintained with Sp 6×, which achieved a shorter acquisition time less than half of PI 2×.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 41 publications
(35 reference statements)
5
44
1
Order By: Relevance
“…From our results, CS techniques also can reduce the SENSE ghost artifacts, highlight the blood signal in the blood vessel, and suppress the background signal. Similar findings have been found in previous studies that the image quality of CS‐MRA is higher than MRA which only using a parallel imaging technique, with more than an acceleration factor of 3 . CS‐MRA scan was successfully performed in all enrolled patients without any technical problems in our study, which demonstrated its good feasibility and stability, consistent with a previous study …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From our results, CS techniques also can reduce the SENSE ghost artifacts, highlight the blood signal in the blood vessel, and suppress the background signal. Similar findings have been found in previous studies that the image quality of CS‐MRA is higher than MRA which only using a parallel imaging technique, with more than an acceleration factor of 3 . CS‐MRA scan was successfully performed in all enrolled patients without any technical problems in our study, which demonstrated its good feasibility and stability, consistent with a previous study …”
Section: Discussionsupporting
confidence: 92%
“…Our study had a fair amount of samples enrolled, and showed that the image quality of CS‐MRA was preferable than those of Con‐MRA. The image quality of CS‐MRA is better due to the sparse undersampling and inherently denoising procedure of CS reconstruction, which enhances the contrast of vessels by counteracting background noise …”
Section: Discussionmentioning
confidence: 99%
“…Sparse MRI approaches work very well for CE‐MRA because bright signals are sparsified within a low background signal with high contrast‐to‐noise ratio, which matches the basic assumptions of CS . It also works well for non‐contrast time‐of‐flight (TOF) MRA due to sparsity in k ‐space …”
Section: Introductionmentioning
confidence: 82%
“…CS application for non‐contrast TOF‐MRA has been done in previous papers. A retrospective approach using 100% sampled raw data of TOF‐MRA was feasible to assess the reconstructed images with various undersampling rates and various CS reconstruction parameters for the NESTA algorithm In another previous study of the non‐contrast TOF‐MRA adopted CS algorithm mFISTA with prospective undersampling, various undersampling rates were compared in healthy volunteers . Sparse‐TOF can achieve better image quality relative to PI TOF at higher acceleration factors …”
Section: Discussionmentioning
confidence: 99%
“…This algorithm reconstructs undersampled MR images through l1 minimization using the property of sparsity when transforming an MR image into a specific domain (such as a wavelet or a discrete cosine transform). Recent studies have demonstrated the clinical feasibility of fast TOF MRA using a compressed sensing‐based iterative method …”
Section: Introductionmentioning
confidence: 99%